2015
DOI: 10.1186/s12929-015-0155-x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging of endogenous enzyme activities using luminescent 1,2-dioxetane compounds

Abstract: BackgroundHere we present a non-invasive imaging method for visualizing endogenous enzyme activities in living animals. This optical imaging method is based on an energy transfer principle termed chemically initiated electron exchange luminescence (CIEEL). The light energy is provided by enzymatic activation of metastable 1,2-dioxetane substrates, whose protective groups are removed by hydrolytic enzymes such as β-galactosidase and alkaline phosphatase. In the presence of a nearby fluorescent recipient, the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
0
15
0
1
Order By: Relevance
“…While several recent studies demonstrated in vivo activation of specific fluorogenic substrates, most of these involved secreted enzymes or enzymes localized to the external face of the plasma membrane, [19] and there have been no in vivo screens evaluating the substrate specificity of its endogenous hydrolases. Given the high conservation and abundance of hydrolases in the genomes of most organisms, [20] the links between esterase activity and diseases ranging from cancer to microbial infections, and recent studies suggesting cell type-specific differences in esterase activity, there is a critical need for a more detailed understanding of these enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…While several recent studies demonstrated in vivo activation of specific fluorogenic substrates, most of these involved secreted enzymes or enzymes localized to the external face of the plasma membrane, [19] and there have been no in vivo screens evaluating the substrate specificity of its endogenous hydrolases. Given the high conservation and abundance of hydrolases in the genomes of most organisms, [20] the links between esterase activity and diseases ranging from cancer to microbial infections, and recent studies suggesting cell type-specific differences in esterase activity, there is a critical need for a more detailed understanding of these enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…made a significant breakthrough and extended the applications of Schaap's dioxetane‐based chemiluminescence to bioimaging and biosensing in vivo [82] . However, the extremely low chemiluminescence signal was observed under physiological conditions due to the quenching effect of water molecules [83] . To amplify the chemiluminescence emission signal, the researchers have adopted the following methods: (1) the formation of polymers, in which the dioxetane unit used as a polymer monomer [84] .…”
Section: Activatable Chemiluminescent Probesmentioning
confidence: 99%
“…Today, enzymes have been put at work and optically acquired images have been significant in helping researchers to understand biological processes compared to abstract measurements [59]. Specifically, live-cell imaging with optical microscopy methods is powerful because they enable real-time detection of cellular processes [60]. Optical events are detected using bioluminescent and fluorescent probes that emit radiation at near-infrared or visible wavelengths, which are detected using optical cameras [60].…”
Section: Optical Detection Techniquesmentioning
confidence: 99%
“…Specifically, live-cell imaging with optical microscopy methods is powerful because they enable real-time detection of cellular processes [60]. Optical events are detected using bioluminescent and fluorescent probes that emit radiation at near-infrared or visible wavelengths, which are detected using optical cameras [60]. Optical methods have been used in detecting analytes because of their simple application.…”
Section: Optical Detection Techniquesmentioning
confidence: 99%